A review on fundamental combustion characteristics of syngas mixtures and feasibility in combustion devices. (August 2021) - Jithin, E.V.; Raghuram, G.K.S.; Keshavamurthy, T.V.; Velamati, Ratna Kishore; Prathap, Chockalingam; Varghese, Robin John
Abstract: Syngas is a promising alternative fuel due to clean combustion with lower greenhouse gas emissions. The multi-component fuel mixture primarily consists of hydrogen, carbon monoxide, nitrogen, carbon dioxide and traces of moisture. The composition of syngas strongly depends on the feedstock and the choice of production method. The wide compositional variability of syngas poses hurdles in developing appliances such as burners and combustion chambers. This review summarizes the recent research on syngas' fundamental combustion characteristics, such as laminar and turbulent burning velocity. The burning velocity prediction capabilities of various reaction mechanisms were analyzed. Comparing the laminar burning velocity predictions using different kinetic schemes with available experimental data in the literature establishes the validity of kinetic schemes. A considerable discrepancy is observed between the experimental data and the present numerical predictions for elevated temperatures at different equivalence ratios. The recent developments in syngas burners, stability regimes, and the need for laminar/turbulent burning velocity data at high temperatures and pressure to improve computational modeling of industrial syngas burners are emphasized. The existing research gap in burners to accommodate syngas with the higher mole fraction of hydrogen is also explored. Highlights: The article summarizes research in understanding the fundamental combustion characteristics of syngas. This review highlights the recent developments in syngas burners and stability regimes. The need for burning velocity data in industrial syngas burner development is discussed. Existing research gap in using syngas with high H2 content in burners is highlighted.